GLOBAL COLONIALITY AND THE CHALLENGES OF CREATING AFRICAN FUTURES (The Strategic Review for Southern Africa, 2020)
Can Africans create African futures within a modern world system structured by global coloniality? Global coloniality is a modern global power structure that has been in place since the dawn of Euro-North American-centric modernity. This modernity is genealogically and figuratively traceable to 1492 when Christopher Columbus claimed to have discovered a 'New World'. It commenced with enslavement of black people and culminated in global coloniality. Today global coloniality operates as an invisible power matrix that is shaping and sustaining asymmetrical power relations between the Global North and the Global South. Even the current global power transformations which have enabled the re-emergence of a Sinocentric economic power and deWesternisation processes including the rise of South-South power blocs such as BRICS, do not mean that the modern world system has now undergone genuine decolonisation and deimperialisation to the extent of being amenable to the creation of other futures. Global coloniality continues to frustrate decolonial initiatives aimed at creating postcolonial futures free from coloniality. The article posits that global coloniality remains one of the most important modern power structures that constrain and limit African agency. To support this proposition, the article delves deeper into an analysis of the architecture and configuration of current asymmetrical global power structures; unmasks imperial/colonial reason embedded in Euro-North American-centric epistemology as well as the problem of Eurocentrism; and unpacks the Cartesian notions of being and its relegation of African subjectivity to a perpetualstate of becoming. Within this context, Africans have emerged as fighting subjects for a new world order that is decolonised, deimperialised, open to the emergence of new humanism and African futures.